Florida 4-H Tailgate: Make Your Own Dry Rub - Brian Estevez; Heather Kent; Jereme Johnson; Haylee Linam; Nick Simmons; Murilo Morata (EDIS)
Dry rubs are a delicious way to season protein and vegetables for the grill. There are four flavor components to a dry rub: spicy, salty, sweet, and savory. This publication lists traditional herbs and spices for each component to get you started designing your own dry rub.